The distribution and biological aspects of Indonesian short-fin eel, Anguilla bicolor bicolor and giant mottled eel, Anguilla marmorata in the northwest of Peninsular Malaysia - Hamzah, Nur Illiani; Abd Khalil, Nurliyana; Azmai, Mohammad Noor Amal; Ismail, Ahmad; Zulkifli, Syaizwan Zahmir (Malaysian Nature Society, 2015)
This study describes the distribution and biology of Indonesian short-fin eel, Anguilla bicolor bicolor and giant mottled eel, Anguilla marmorata collected in the northwest of Peninsular Malaysia. A total of 33 specimens of A. b. bicolor were collected from Sungai Batu Pahat, Kuala Perlis and downstream of Sungai Pinang, while five specimens of A. marmorata were collected from the upper stream of Sungai Pinang. The range of body mass and total length of A. b. bicolor and A. marmorata were 85.2-2012.1 g and 275.0-905.0 mm; and 240.1- 830.1g and498.0-756.0 mm, respectively. The individual gonadosomatic index (IG) value for A. b. bicolor collected from Perlis and Pulau Pinang indicated that 90.0% and 39.1% of the samples were in mature stages, respectively, while for A. marmorata,the individual IG value indicates that all of the samples were still immature. The occurrence and distribution of A. b. bicolor was firstly reported in Perlis, Malaysia.